IMPACT OF CIRCUMCISION EXPERIENCES ON SURGICAL ANXIETY IN ADULTHOOD: A COMPREHENSIVE STUDY (International Journal of Scientific Pediatrics, 2023)
Objective: Our purpose was to investigate whether patients who had previously undergone circumcision (considering the timing and method of the procedure) experienced altered levels of anxiety when facing other surgeries later in life.Materials and methods: It was investigated to what extent circumcision affects surgical anxiety. Patients who applied to our clinic to undergo surgery due to any disease in adulthood were included. The surgery anxiety scale was used for collection of the data. Results: This study involved 54 men, with an average age of 46.7 years, assessing their surgical anxiety scores in relation to various factors. While 59.3% had one surgery, significant minorities underwent multiple procedures. Regarding anesthesia during surgeries, 61.1% received local, 24.1% spinal, and 14.8% general anesthesia. Notably, 63% of participants were smokers. Previous hospitalization was reported by 51.9%, and 37% had other surgeries. Interestingly, 59.3% had contracted COVID-19. Age of circumcision showed no significant effect on anxiety scores. However, those who underwent forced circumcision (11.1%) had notably higher anxiety scores (p=0.04). Most circumcisions (96.3%) occurred in hospitals, with doctors conducting 81.48% of them. No correlation was found between patients' age during circumcision and current anxiety. Significantly, forced circumcisions led to increased surgical anxiety. Conclusions: Our study suggests that while circumcision's method, location, and performer significantly influence the individual's surgical anxiety in adulthood, the age of circumcision does not play a determining role.
Keywords: cirumcision; surgery; anxiety; trauma